Demokrasi dan E-Government Memetakan Perhatian Dunia Hari ini (Studi Tentang Empat Lembaga Indeksasi) - Tawakkal, George Towar Ikbal (Politeia: Jurnal Ilmu Politik, 2023)
The development of e-government has attracted the attention of many activists and has become the new face of government in the world. E-government is seen as the best collaboration between the public sector and technology and is seen as the success of government innovation. Its role as a channel of interaction between the government and citizens, causes the implementation of e-government to be believed to be in line with the development of democratization. Today, many agencies assess the implementation of e-government. The most common, assessment is in the form of indexes. Among the indexes commonly referred to are The Global Open Data Index (GODI), The E-Government Index (EGI), The National Cyber Security Index (NCSI), and local indexation as an example is Indonesia with the Indonesian E-Government Rating (PeGI). Amid various indicators that underlie these indexes, this article asks the question, what are the main aspects that e-government activists pay attention to? Through a literature review sourced from various institutions that manage the indexes, this article concludes that e-government activists pay more attention to e-government development strategies, and at the same time become the aspect that requires the most attention.